Bargaining with a Residual Claimant: An Experimental Study - Matthew Embrey; Kyle Hyndman; Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2014)
We experimentally investigate a bargaining environment in which players negotiate over a fixed payment to one player, while the other player receives the residual from a random pie realization after subtracting the fixed payment. Contrary to the intuition that risk exposure is detrimental, we show that residual claimants are able to extract a risk premium, which is increasing in risk exposure. In some cases the premium is so high that it is advantageous to bargain over a risky pie rather than a risk-less pie. Contrary to theory, the comparatively less risk adverse residual claimants benefit the most. Moreover, bargaining frictions increase as risk increases, and we document more frequent disagreements as risk increases. When given the chance to choose a less or more risky distribution over which to bargain, residual claimants tend to choose the more risky distribution only when there is the possibility of an equal-split ex-post. Our results suggest that theoretical bargaining models require some separation between the determinants of bargaining power and fair compensation for risk exposure.
Keywords: C71; C92; D81; 330; bargaining; ex-post risk; reference points